From Folke Medicine to Medicine Chemistry: Study, Using in Vitro and Cellular Assays, of Receptors Mechanism Involved in the Activities of Natural Compounds - Micucci, Matteo <1983> (Alma Mater Studiorum - Università di Bologna, 2012)

(untitled)
My Doctorate Research has been focused on the evaluation of the pharmacological activity of a natural extract of chestnut wood (ENC) towards the cardiovascular and gastrointestinal system and on the identification of the active compounds. The ENC has been shown to contain more than 10% (w/w) of phenolic compounds, of which tannins as Vescalgin and Castalgin are the more representative. ENC cardiovascular effects have been investigated in guinea pig cardiac preparations; furthermore its activity has been evalueted in guinea pig aorta strips. ENC induced transient negative chronotropic effect in isolated spontaneously beating right atria and simultaneously positive inotropic effect in left atria driven at 1 Hz. Cardiac cholinergic receptors are not involved in the negative chronotropic effect and positive inotropic effects are not related to adrenergic receptors. In vascular smooth muscle, natural extract of chestnut did not significantly change the contraction induced by potassium (80 mM) or that induced by noradrenaline (1μM). In guinea pig ileum, ENC reduced the maximum response to carbachol in a concentrationdependent manner and behaved as a reversible non competitive antagonist. In guinea pig ileum, the antispasmodic activity of ENC showed a significant antispasmodic activity against a variety of different spasmogenic agents including histamine, KCl, BaCl2. In guinea pig proximal colon, stomach and jejunum, ENC reduced the maximum response to carbachol in a concentrationdependent manner and behaved as a reversible non competitive antagonist. ENC contracted gallbladder guinea pig in a reversible and concentration-dependent manner. This effect does not involve cholinergic and cholecystokinin receptors and it is reduced by nifedipine. ENC relaxed Oddi sphincter smooth muscle. The cholecystokinetic and Oddi sphincter relaxing activities occurred also in guinea pigs fed a lithogenic diet. The cholecystokinetic occurred also in human gallbladder. The Fractionation of the extract led to the identification of the active fraction.